Di-ammonium phosphate (DAP) and plant density improve grain yield, nodulation capacity, and profitability of peas (Pisum sativum L.) on ferralsols in eastern D.R. Congo - Géant Basimine Chuma; Blaise Mulalisi; Jean Mubalama Mondo; Adrien Byamungu Ndeko; Francine Safina Bora; Espoir Mukengere Bagula; Gustave Nachigera Mushagalusa; René Civava (CABI Agriculture and Bioscience)
Abstract Sustaining high crop yield and profitability on marginal soils, such as degraded ferralsols, calls for the use of adequate farming practices. In this study, we assessed for four cropping seasons the effect of di-ammonium phosphate (DAP) fertilizer application doses (100, 150, and 200 kg ha−1) and plant densities (100,000, 166,666, and 250,000 plants ha−1) on growth, yield, nodulation capacity, and profitability of two pea varieties (Adei and Rwanda) under degraded ferralsols in eastern Democratic Republic of Congo (DRC). Results showed that pea growth, yield, nodulation, and profitability were significantly affected by the DAP dose and the plant density. Application of 150 kg ha−1 of DAP improved pea yields from 730 to 1720 kg ha−1 and nodulation from 17 to 22 nodules per plant. The number of active nodules was positively correlated with total number of nodules, DAP doses, yield parameters, and plant height. High grain yield was recorded during the long rainy season (1400 kg ha−1) compared to the short one (930 kg ha−1). All DAP doses were profitable according to the agronomic efficiency (AE) and value–cost ratio (VCR) analyses. For improved and profitable pea production on degraded South-Kivu ferralsols, applying 150 kg ha−1 of DAP combined with low plant density are to be recommended and preferably in the long rainy season.